Assessment of functional connectivity for African savanna elephants (Loxodonta africana) in the Great Limpopo Transfrontier Conservation Area - Rowland, Roxanne (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScConsEcol)--Stellenbosch University, 2025.